Viscoelastic Haemostatic Assays in Cardiovascular Critical Care - Aniket S Rali (Radcliffe Medical Media, 2021)
The initiation and management of anticoagulation is a fundamental practice for a wide variety of indications in cardiovascular critical care, including the management of patients with acute MI, stroke prevention in patients with AF or mechanical valves, as well as the prevention of device thrombosis and thromboembolic events with the use of mechanical circulatory support and ventricular assist devices. The frequent use of antiplatelet and anticoagulation therapy, in addition to the presence of concomitant conditions that may lead to a propensity to bleed, such as renal and liver dysfunction, present unique challenges. The use of viscoelastic haemostatic assays provides an additional tool allowing clinicians to strike a delicate balance of attaining adequate anticoagulation while minimising the risk of bleeding complications. In this review, the authors discuss the role that viscoelastic haemostatic assay plays in cardiac populations (including cardiac surgery, heart transplantation, extracorporeal membrane oxygenation, acute coronary syndrome and left ventricular assist devices), and identify areas in need of further study.